(untitled) (Medico Legal Update, 2021)
Background: Tuberculosis is a direct infectious disease caused by TB germs (Mycobacterium Tuberculosis). Indonesia is ranked third in the world, with the largest incidence of tuberculosis after China and India, with 845,000 cases or 315/100,000 in 2019. The study was intended to analyze the coverage of treatment of all cases, the percentage of poor people by province and the ratio of public health centre per sub-district in the province to the success of tuberculosis treatment in all provinces in Indonesia in 2019. Methods: The ecological approach is carried out using secondary data from the Ministry of Health of the Republic of Indonesia in the form of Health Profile of the Republic of Indonesia in 2019 and Data and Information: Health Profile of Indonesia in 2019. Data from 34 provinces in Indonesia related to the success rate of TB treatment, the coverage of treatment of all TB cases, the percentage of poor people by province and the ratio of public health centre per sub-district in the province using cross tabulation. Results: The results showed that the success rate of TB treatment in Indonesia in 2019 was in the moderate category in line with the coverage of all TB cases, the percentage of poor people by province and the ratio of puclic health centre per sub-district in the province which is also in the moderate category. Conclusion: Efforts to monitor and record cases and treatment of TB patients need to be improved to improve TB treatment coverage. Improving the economy of the community and equalizing the availability of public health centre are also very important to improve the success of TB treatment.